1995
DOI: 10.1111/j.1365-2958.1995.mmi_18040593.x
|View full text |Cite
|
Sign up to set email alerts
|

Photonic detection of bacterial pathogens in living hosts

Abstract: The study of pathogenic processes is often limited to ex vivo assays and cell-culture correlates. A greater understanding of infectious diseases would be facilitated by in vivo analyses. Therefore, we have developed a method for detecting bacterial pathogens in a living host and used this method to evaluate disease processes for strains of Salmonella typhimurlum that differ in their virulence for mice. Three strains of Salmonella were marked with bioluminescence through transformation with a plasmid conferring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
390
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(398 citation statements)
references
References 41 publications
6
390
0
1
Order By: Relevance
“…This PRG gene activated by loxP-dependent recombination allowed us to image noninvasively the PRG expression by microPET and to identify the tissues that express the Cre recombinase. Although development of a cooled charged coupled device (CCD) camera also allows the noninvasively imaging of the expression of firefly luciferase gene in small animals, 20,21 it is limited by the lack of tomographic information and full quantitation capability.…”
Section: Discussionmentioning
confidence: 99%
“…This PRG gene activated by loxP-dependent recombination allowed us to image noninvasively the PRG expression by microPET and to identify the tissues that express the Cre recombinase. Although development of a cooled charged coupled device (CCD) camera also allows the noninvasively imaging of the expression of firefly luciferase gene in small animals, 20,21 it is limited by the lack of tomographic information and full quantitation capability.…”
Section: Discussionmentioning
confidence: 99%
“…25 Contag and colleagues were the first to utilize bioluminescent strains of pathogens to study infection longitudinally in mice. 26 Subsequent studies have proven the value of BLI over conventional methods in studying disease and therapeutic interventions in animals. 25 More recently, this group generated bioluminescent S. aureus Xen29 for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that if the light emitted in vivo from the luciferaseexpressing cells is sufficient, it can be detected in anesthetized animals through the tissues with a sensitive CCD camera. [24][25][26] We thus used this new method to visualize the luciferase activity in vivo and we also used the standard procedure to measure it on tissue samples. Indeed, we could easily detect the luciferase activity after an IME (Figure 2a).…”
Section: Intrasplenic Vs Intramuscular Gene Transfer Efficiencymentioning
confidence: 99%